2009
DOI: 10.1021/jp901953f
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Chemical Synthesis of Silver Telluride Nanowires

Abstract: We have developed a room-temperature solution-phase route for the preparation of one-dimensional silver telluride nanowires (Ag 2 Te NWs). The Ag 2 Te NWs of 600 nm length and 20 nm diameter were synthesized by the reaction of tellurium nanowires (Te NWs) with silver nitrate (AgNO 3 ) in water. We propose that Te NWs act as the template and the reducing agent simultaneously, enabling the formation of polycrystalline Ag 2 Te NWs. Various microscopic and spectroscopic tools, such as HRTEM, SEM, EDAX, XRD, DSC, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 47 publications
8
69
0
Order By: Relevance
“…[4][5][6][7][8][9] Moreover, the recent discovery of the surface-enhanced Raman scattering of Ag 2 Te nanowires has generated intense interest from both fundamental research and application point of views. [10] Thus, a variety of synthetic strategies have been developed to explore novel architectures and morphological patterns of this important functional material. For instance, Ag 2 Te nanocrystals were synthesized from a mixture of AgNO 3 and Te in ethylene glycol or ethylenediamine by ultrasonication at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] Moreover, the recent discovery of the surface-enhanced Raman scattering of Ag 2 Te nanowires has generated intense interest from both fundamental research and application point of views. [10] Thus, a variety of synthetic strategies have been developed to explore novel architectures and morphological patterns of this important functional material. For instance, Ag 2 Te nanocrystals were synthesized from a mixture of AgNO 3 and Te in ethylene glycol or ethylenediamine by ultrasonication at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Alternatively, a room-temperature solution-phase route was developed for the preparation of Ag 2 Te nanowires. [10] Ag 2 Te nanomaterials with a large surface-to-volume ratio are attracting ever-increasing attention. In particular, nanosheets are considered ideal candidates for probing size-and dimensionality-dependent physical or chemical phenomena as well as for applications in nanodevices due to their large aspect ratio and faceting nature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ag 2 Te NWs were synthesized by a composite hydroxide-mediated method, where AgNO 3 and Te powder were heated at 498 K in a Teflon vessel containing ethylenediamine and hydrazine hydrate [23]. Samal and Pradeep [24] have developed a room-temperature solution-phase route for the preparation of 1D Ag 2 Te NWs. In addition, our research group has more recently reported the synthesis and electrical properties of individual Ag 2 Te NWs via a hydrothermal process [25].…”
Section: Introductionmentioning
confidence: 99%
“…These 1D Te nanostructures have further been utilised as a template for synthesizing different metal telluride nanostructures. [27][28][29][30][31][32][33] While several of these single phase NWs have been synthesized, recent efforts have been directed towards the facile synthesis of heterostuctured NWs though reports have been very few. 34 These 1D heteronanostructures belong to multiple types.…”
Section: Introductionmentioning
confidence: 99%